A Guide to Flow Cytometry: Components, Basic Principles, Experimental Design, and Cancer Research Applications. Issue 3 (22nd March 2023) - El‐Hajjar, Layal; Ali Ahmad, Fatima; Nasr, Rihab
Abstract: Flow cytometry (FCM) is a state‐of‐the‐art technique for the qualitative and quantitative assessment of cells and other particles' physical and biological properties. These cells are suspended within a high‐velocity fluid stream and pass through a laser beam in single file. The main principle of the FCM instrument is the light scattering and fluorescence emission upon the interaction of the fluorescent particle with the laser beam. It also allows for the physical sorting of particles depending on different parameters. A flow cytometer comprises different components, including fluidic, optics, and electronics systems. This article briefly explains the mechanism of all components of a flow cytometer to clarify the FCM technique's general principles, provides some useful guidelines for the proper design of FCM panels, and highlights some general applications and important applications in cancer research. © 2023 Wiley Periodicals LLC.